A case of angioimmunoblastic T-cell lymphoma with high serum VEGF preceded by RS3PE syndrome. Issue 2 (3rd March 2016) - Tabeya, Tetsuya; Sugaya, Toshiaki; Suzuki, Chisako; Yamamoto, Motohisa; Kanaseki, Takayuki; Noguchi, Hiroko; Naishiro, Yasuyoshi; Ishida, Tadao; Takahashi, Hiroki; Shinomura, Yasuhisa
Abstract : We report the case of a 76-year-old man diagnosed with angioimmunoblastic T-cell lymphoma (AITL) with high serum vascular endothelial growth factor (VEGF) preceded by Remitting seronegative symmetrical synovitis with pitting edema syndrome. He suffered respiratory discomfort caused by large amounts of pleural effusion. Interestingly, changes in serum VEGF measured over time were similar to changes in pleural effusion. Whether VEGF is related to the pathological condition of AITL is a very important question.